2018
DOI: 10.1097/cad.0000000000000637
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fibroblast growth factor receptor-signaling sensitizes imatinib-resistant gastrointestinal stromal tumors to low doses of topoisomerase II inhibitors

Abstract: The acquired resistance of gastrointestinal stromal tumors (GISTs) to the targeted-based therapy remains the driving force to identify the novel approaches that are capable of increasing the sensitivity of GISTs to the current therapeutic regimens. Our present data show that BGJ398, a selective fibroblast growth factor receptor (FGFR) inhibitor, sensitizes imatinib (IM)-resistant GIST cells with receptor tyrosine kinase (RTK) switch (loss of c-KIT/gain of pFGFR2a) to the low doses of topoisomerase II inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…For example, we showed that IM-resistant GIST cell lines established in our lab harbored a receptor-tyrosine kinase (RTK) switch (loss of c-KIT/gain of FGFR2), thus revealing the possibility of FGFR activation after prolonged IM exposure [ 21 ]. Moreover, we observed that aberrant FGFR signaling in IM-resistant GIST cells has an impact on GIST resistance to IM and topoisomerase II inhibitors [ 21 , 22 ]. The latter might be due to the ability of FGFR signaling to maintain effective repair of DNA double-strand breaks (DSBs) via a homology-mediated pathway [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we showed that IM-resistant GIST cell lines established in our lab harbored a receptor-tyrosine kinase (RTK) switch (loss of c-KIT/gain of FGFR2), thus revealing the possibility of FGFR activation after prolonged IM exposure [ 21 ]. Moreover, we observed that aberrant FGFR signaling in IM-resistant GIST cells has an impact on GIST resistance to IM and topoisomerase II inhibitors [ 21 , 22 ]. The latter might be due to the ability of FGFR signaling to maintain effective repair of DNA double-strand breaks (DSBs) via a homology-mediated pathway [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we observed that aberrant FGFR signaling in IM-resistant GIST cells has an impact on GIST resistance to IM and topoisomerase II inhibitors [ 21 , 22 ]. The latter might be due to the ability of FGFR signaling to maintain effective repair of DNA double-strand breaks (DSBs) via a homology-mediated pathway [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, BGJ398, a selective FGFR1-3 inhibitor, has a high potency to sensitize IM-resistant GIST cells to the topoisomerase II inhibitors, doxorubicin and etoposide. A substantial decrease of cell viability, proliferation and growth was found in IM-resistant GIST cells simultaneously treated with FGFR-and DNA-topoisomerase II inhibitors [18]. Based on this data, we wondered whether inhibition of FGFRsignaling might have an impact on DNA damage signaling and repair in GIST cells, especially on tumor cells that acquired IM-resistant phenotype over IM-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown previously that GIST cell lines and patient-derived IM-resistant primary GIST cells are sensitive to certain chemotherapeutic agents, such as topoisomerase II inhibitors and transcriptional inhibitors [19,20]. Based on our previous data illustrating that inhibition of FGF-signaling in GIST effectively sensitized them to DNA damaging agents (e.g., topoisomerase II inhibitors) [18], we sought to examine whether it might be due to decreased efficiency of DDR mechanisms involved in repair of the double-strand breaks (DSBs).…”
Section: Fgfr Inhibition Delays Dna Dsbs Repair Im-resistant Gistsmentioning
confidence: 94%
See 1 more Smart Citation